PENERAPAN PERANGKAT PEMBELAJARAN PBL UNTUK MENINGKATKAN KEMAMPUAN ANALYTICITY PADA SISWA SMP - Isnainiwati; Arafah, Rezqy Ayu Devi; Widijastuti, Rara Sri (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
This study aims to examine the effectiveness of Problem Based Learning (PBL)-based learning tools in improving students’ analyticity skills in mathematics. The research employed a quasi-experimental method with a Pretest–Posttest Control Group Design. The population consisted of seventh-grade students at SMP Negeri 1 Rogojampi in the even semester of the 2022/2023 academic year, with the sample selected using purposive sampling, comprising one experimental class and one control class. The research instruments included analyticity skill tests, observation sheets for learning implementation, and documentation. The results showed that the implementation of PBL learning tools significantly improved students’ analyticity skills. The average posttest score of the experimental class increased from 34.84 to 80.39 with a N-Gain of 0.71 (high category), while the control class increased from 22.42 to 55.81 with a N-Gain of 0.43 (medium category). Observations indicated that the PBL stages were applied systematically and effectively, encouraging students to actively discuss, analyze information, present solutions, and reflect on the learning process. Based on these findings, the implementation of PBL-based learning tools is proven effective in enhancing students’ analyticity skills and can serve as an alternative strategy for more meaningful and contextual mathematics learning.